Exploring the landscape of quality 4.0: a comprehensive review of its benefits, challenges, and critical success factors - Maram Mahin; Nasser Kadasah; Abdullah Alsabban; Saja Albliwi (Production and Manufacturing Research: An Open Access Journal)
Quality 4.0 (Q4.0), integrates new digital technologies with traditional quality management to improve operational excellence across industries. This literature review, adhering to PRISMA principles, examines papers from 2015 to 2023, focusing on the benefits, challenges, and critical success factors of Q4.0 implementation. Results highlight significant benefits, including enhanced operational efficiency and innovation, while identifying skill gaps, restrictions on resources, and substantial expenses in investment as major challenges. Strategic leadership and comprehensive frameworks are essential for overcoming these challenges and facilitating successful Q4.0 implementation. These insights are intended to assist organizations in navigating the intricate landscape of Quality 4.0.